Theoretical fundamentals of study of values and value orientations in management of psychological scientific space - Мельничук, Світлана Миколаївна; Мельничук, С. М.; Мельничук, Светлана Николаевна; Melnychuk, Svitlana M.; Курова, Анастасія Володимирівна; Курова, А. В.; Курова, Анастасия Владимировна; Kurova, Anastasiia V.; Швецова, Ірина Вікторівна; Швецова, І. В.; Швецова, Ирина Викторовна; Shvetsova, Iryna V.; et al. (Allied Business Academies, 2021)
The qualitative analysis of modern and classical literature in the field of scientific achievement and possibilities of management of psychological component is carried out in the work. The article considers and conducts theoretical studies of the phenomenon of values and value orientations and their management, draws qualitative conclusions that each psychological theory explains them differently, namely, sees behavior as a result of associative learning, humanists see values in the "self" of the individual and connect them to human needs. Scientists around the world argue for the inclusion in the mechanisms of activity and behavior of the individual and conclude that value orientations are characterized by two properties- meaning and personal content.

У роботі проведено якісний аналіз сучасної та класичної літератури в галузі наукових досягнень та можливостей управління психологічною складовою. У статті розглядаються та проводяться теоретичні дослідження феномену цінностей та ціннісних орієнтацій та управління ними, робляться якісні висновки про те, що кожна психологічна теорія пояснює їх по-різному, а саме розглядає поведінку як результат асоціативного навчання, гуманісти бачать цінності в «я» особистості та пов’язують їх із потребами людини. Вчені всього світу виступають за включення в механізми діяльності та поведінки особистості і приходять до висновку, що ціннісні орієнтації характеризуються двома властивостями – змістом і особистісним змістом.
Melnychuk S. Theoretical fundamentals of study of values and value orientations in management of psychological scientific space / S. Melnychuk, A. Kurova, I. Shvetsova, O. Shcherbakova, O. Tsilmak, L. Luts // Journal of Management Information and Decision Sciences. - Vol. 24. - Issue 2. - Allied Business Academies, 2021. – P. 1-6.
Keywords: value orientations; reinforcement value; value of needs; value judgments; moral standards; personal values; ціннісні орієнтації; підкріплення цінності; значення потреб; оціночні судження; моральні норми; особисті цінності; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology